TRACER STUDY OF GRADUATES QUALITY ASSESMENT BY THE HEAD ROOM OF HOSPITAL IN DISTRICT BOJONEGORO IN YEAR 2012 - RAHMAWATI, RAHMAWATI (Asuhan Kesehatan : Jurnal Ilmiah Ilmu Kebidanan dan Keperawatan, 2014)
Educational institutions established containing a moral and social responsibility of the government, students, the community and the stakeholders. That responsibility implies that education held should give priority to quality education in order to achieve a good quality of graduates according to expectations of all stakeholders. To identify the needs of the  competencies of graduates, Tracer study provides information about the needs of the market and the relevance between education and employment outcomes of graduates . Tracer study results will provide clear direction on planning education to have appropriate quality expectations of stakeholders. The purpose of this study was to identify the quality graduates assessment of third diploma of Nursing  Akes Rajekwesi Bojonegoro through tracer studies in the scope of Bojonegoro hospital in 2012.The research is descriptive with survey approach. The population is the entire head room of  Hospital in Bojonegoro  in 2012 with a sample size of 35 head room of  hospital in Bojonegoro . The variable research was quality of  graduates that includes cognitive, affective, and psychomotor assesment. The research instrument was a questionnaire given to the head room of the hospital to assess the quality of graduates who have worked in the hospital and still an apprentice. Data was processed and tabulated by scoring and presented by procentage tabular.The results showed that the assessment of the quality of Nursing graduates of third diploma Akes Rajekwesi Bojonegoro that have already employed by the head room of hospital was a good majority (82.9%) while the alumni who carry out an internship in good category (44.8%) and sufficient (48.3% ).Based on the research results, it is necessary the participation of Internal quality assurance of institution, lecturer, and a whole range of leaders to commit in order to improve the quality of graduates. Key word : Tracer study, assesment, headroom, graduates